Effect of different disinfecting procedures on the hardness and color stability of two maxillofacial elastomers over time (Journal of Applied Oral Science, 2013)
Objective Disinfection procedures often cause deterioration in a maxillofacial prosthesis. Color and hardness alterations could lead to a replacement of the prosthesis. Material and Methods An experimental chlorinated polyethylene (CPE) and a commercial polydimethyl siloxane (PDMS) sample were treated with four different disinfection procedures for a period which simulates 1 year of clinical service. The applied disinfection procedures included microwave exposure and immersion in three solutions, sodium hypochlorite, neutral soap and a commercial disinfecting soap. Shore A hardness (∆H) and color differences (∆E) were determined before and after each procedure. All data were analyzed by Two Way Analysis of Variance (ANOVA) and Tukey's post hoc tests at a level of α=0.05. Results The samples presented significant alterations in color and hardness after the different disinfection treatments. The color differences (∆E) were at least eye detectable in all cases and clinically unacceptable in most of the cases, with values ranging from 1.51 to 4.15 and from 1.54 to 5.92 for the PDMS and CPE material, respectively. Hardness was decreased after all the disinfection procedures in the PDMS, while for the CPE, a decrement was observed after disinfection with sodium hypochlorite and neutral soap and an increment after microwave exposure and the disinfection with a commercial antimicrobial agent. The PDMS samples presented greater alterations in color and hardness after disinfection with sodium hypochlorite solution, while the microwave exposure caused negligible effects. The CPE samples were affected most after disinfection when treated with neutral soap, and more slightly when disinfected with sodium hypochlorite solution. Conclusions The disinfection procedures caused alterations in color and hardness of the examined materials. The most suitable disinfection procedure for the PDMS material is microwave exposure, while disinfection with sodium hypochlorite solution is not recommended. The CPE material is suggested to be disinfected with sodium hypochlorite solution and the use of neutral soap is not recommended. Comparing the two materials, the PDMS material is most color stable, while the CPE material presented fewer changes in hardness.